Enhancing Links of Poor Farmers to Markets : A Practice Review for Economic Inclusion in Zambia - Sparkman, Tim; Sackett, Jill; Avalos, Jorge; Varghese Paul, Boban (World Bank, Washington, DC, 2022)
This report reviews the experiences of market linkage programs implemented globally, particularly those focused on poor smallholders, including women, as beneficiaries and farmers who participated in government social safety net schemes. The report highlights lessons learned by program implementers, governments, and other stakeholders related to efforts to link extremely poor households to productive markets. The research was commissioned to inform potential links between two World Bank projects that are currently supporting the economic inclusion of poor households in Zambia. The supporting women’s livelihood (SWL) program of the Girls’ Education and Women’s Empowerment and Livelihoods (GEWEL) Project provides a comprehensive package to promote economic inclusion among women from the poorest households. A second project, the Zambia Agribusiness and Trade Project (ZATP), enhances access to markets by linking producer organizations and high-growth small and medium-size enterprises to buyers (commercial off-takers) by facilitating productive alliances (commercial agreements between a producer organization and a commercial off-taker) and providing matching grants and technical support. A diagnostic of the status of and constraints facing SWL beneficiaries with respect to market linkages highlights the lack of upstream value chain linkages for them. The World Bank will provide technical assistance to the government of Zambia, through relevant ministries, to operationalize a mechanism, at scale, for forging market linkages by SWL households by linking them to ZATP beneficiaries. This report reviews and highlights the experiences of similar market linkages programs implemented globally, in an attempt to answer key questions raised by the program. This report describes operational considerations that may be relevant to the ZATP-GEWEL project context. It provides recommendations to guide the next steps in developing the ZATP-GEWEL pilot.